Space weapons : earth wars - Preston, Bob, 1951- (Online Rand research documents., 2002)
An exploration of the possibility, utility, legalities and limitations of the military use of space, specifically the use in space of weapons or defences for terrestrial conflict. The authors define and classify these weapons, describe their attributes, and explain how they might be used.